2012
DOI: 10.1093/neuonc/nos135
|View full text |Cite
|
Sign up to set email alerts
|

In vivo models of primary brain tumors: pitfalls and perspectives

Abstract: Animal modeling for primary brain tumors has undergone constant development over the last 60 years, and significant improvements have been made recently with the establishment of highly invasive glioblastoma models. In this review we discuss the advantages and pitfalls of model development, focusing on chemically induced models, various xenogeneic grafts of human cell lines, including stem cell–like cell lines and biopsy spheroids. We then discuss the development of numerous genetically engineered models avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
270
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(281 citation statements)
references
References 110 publications
4
270
1
6
Order By: Relevance
“…As stated in a review [31] ''preclinical studies must use intracranial models that exhibit appreciable tumor-infiltrated normal brain protected by the BBB in order to be most informative''. This was fulfilled with the neurosphere-based tumor model used in this study in line with data provided by Huszthy et al [32]. Additionally, neurosphere-based models more closely resemble the original patient tumor molecularly than adherent monolayer-based models like U87MG xenografts [33][34][35].…”
Section: Discussionsupporting
confidence: 83%
“…As stated in a review [31] ''preclinical studies must use intracranial models that exhibit appreciable tumor-infiltrated normal brain protected by the BBB in order to be most informative''. This was fulfilled with the neurosphere-based tumor model used in this study in line with data provided by Huszthy et al [32]. Additionally, neurosphere-based models more closely resemble the original patient tumor molecularly than adherent monolayer-based models like U87MG xenografts [33][34][35].…”
Section: Discussionsupporting
confidence: 83%
“…Instead, all genetically engineered mice (GEM) have in common that they require a "critical mass" of recombined cells, usually with initial mutations of multiple genes, to develop tumors. Despite significant advances in refining the population of cells, there are also limitations to the specificity of targeting stem progenitor cells in GEM (54,55). Because of the simultaneous recombination of cells with identical mutations, GEM may not reflect all aspects of the biology of human gliomas, which are known to show significant intratumoral heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the plasticity of the tumor cell population may be less pronounced than in patient tumors. The Bjerkvig laboratory has demonstrated that highly infi ltrative brain tumors with a stemlike phenotype can be established by xenotransplantation of human GBMs into immunodefi cient nude rats (Huszthy et al 2012 ). The model consists of the implantation of spheroids from human glioma patient tumors.…”
Section: Methods To Investigate Angiogenesis and Invasion In Gbmmentioning
confidence: 99%